PENGARUH INTEGRITAS, INDEPENDENSI, DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS HASIL KERJA AUDITOR: DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERATING (STUDI KASUS BPKP PERWAKILAN DIY) - Mangesti, Citra Ari; Ayem, Sri; Erawati, Teguh (Universitas Ahmad Dahlan, 2019)
This research examine to analyze and find out whether the auditor's ethics strengthen the influence of auditor's integrity, independence, and professionalism on the quality of the auditor's work. The population in this research is the Financial and Development Supervisory Agency (BPKP). The sample in this research is the auditor who has registered and worked at the Financial and Development Supervisory Agency, have a minimum educational background in Bachelor Accounting. The sampling method uses nonprobability with purposive sampling. Data collection was carried out through the distribution of questionnaires was thirty one questionnaires. Data were analyzed using SPSS version twenty five. The data analysis technique used was multiple linear regression analysis. For moderating analysis were using Moderated Regression Analysis (MRA). T test results show that integrity, independence, and professionalism have a positive effect on the quality of the work of auditors. Auditor ethics have a positive effect and moderate the relationship between the influence of integrity, independence, and professionalism of auditors.